2017
DOI: 10.1177/1367493517705736
|View full text |Cite
|
Sign up to set email alerts
|

A study of the stressors and coping behaviors of parents of Chinese hemophilic children

Abstract: To understand the stressors experienced by parents of hemophiliac children in China and the coping behaviors utilized, semi-structured interviews were conducted with parents of 158 Chinese hemophiliac children. We administered the Coping Health Inventory for Parents to determine coping behaviors. Parents' main stressors were in the domains of children's illness and physical condition, economic problems, and so on. Parents engaged in various positive coping behaviors to manage these stressors. The helpfulness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Arabic is the official and mother tongue language and Islam is the main religion in Jordan 12 . The other studies which their findings were compared with the findings of the present study included caregivers from UK 13–14 ; different European countries, including Germany, Italy, Netherlands, Poland, Sweden and Turkey 14 ; Sweden 15 ; Norway 16 ; United States 17 ; and China 18 …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Arabic is the official and mother tongue language and Islam is the main religion in Jordan 12 . The other studies which their findings were compared with the findings of the present study included caregivers from UK 13–14 ; different European countries, including Germany, Italy, Netherlands, Poland, Sweden and Turkey 14 ; Sweden 15 ; Norway 16 ; United States 17 ; and China 18 …”
Section: Discussionmentioning
confidence: 90%
“…In China, Peng et al 18 . reported that the most common stressors among caregivers of children with haemophilia are related to the illness and physical condition of the children, economic problems and child treatment‐related stressors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the parents communicated in a more direct manner when their children exhibited disruptive behavior, commanding them to effect a desired change in their behavior. Parental management of a child’s behavior using both indirect and direct communication has been shown to be a positive coping strategy in the Chinese cultural context (Peng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In China, unpredictability was associated negatively with parents' ability to cope (r = −0.225;p < 0.05) (He et al, 2016). Parents regarded "family members working together as a unit" as the most helpful coping strategy, and "allowing myself to be angry" as the least helpful (Peng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%